Logika, Tujuan dan Aspek Sosiologis Hukum Islam: Restrukturisasi Fiqh untuk Perubahan Sosial - JM Muslimin (Al-Ulum, 2019)
Can Islamic law change the conservation paradigm into transformation? If possible, which aspects can be done for this matter? How far the linkage between conventional Islamic law and social adaptation can continue to be elaborated? Where can the linkage aspects between Islamic law, structure, and culture be found? That is among the several questions to be answered in this paper. Reflecting on conventional (Western) law, writing tries to compile the links between aspects of Islamic law, social and cultural structures. The article concludes with an emphasis on the importance of understanding the beginnings of the growing systematization of Islamic law, as well as the relative aspects of systematization and the necessity of understanding the socio-cultural settings that are constantly changing in the current period. So, it can produce transformative Islamic legal patterns. Islamic law that corresponds to social change.